Gambaran Resiliensi Siswa dalam Menghadapi Kecemasan Akademik Selama Pembelajaran Tatap Muka Terbatas Siswa Pada Sekolah Menengah Atas - Tanziilal Dara Sabrina Salsadilla; Rahmulyani Rahmulyani (INDONESIAN COUNSELING AND PSYCHOLOGY, 2022)
This study aims to describe the state of student resilience when faced with academic anxiety during limited face-to-face learning in class X IPA SMA Negeri 1 Labuhan Deli Academic Year 2021/2022. The method used in this research is descriptive quantitative method which is a research which is carried out with the aim of describing the existence of a phenomenon, in this study it is not intended to test hypotheses but only to describe what happens to a certain variable. The sample in this study was 100 students from class X IPA. The scale given contains 43 items related to Resilience and Academic Anxiety. The results of the validation of the research instrument used the product moment correlation analysis technique. In the calculation, it is known that if N = 51 then rtable = 0.279. In accordance with the calculation provisions, it can be said that rcount > r table then the item is declared valid and if rcount < rtable then the item is declared invalid. From the results of the reliability test, the Chronbach Alpha value is (0.710). This value is greater than the rtable value with a significance level of 5% or coefficient > 0.60 then the item is declared reliable. the results of this study found that there are students who have low resilience when facing academic anxiety during limited face-to-face learning. Then gender or gender can affect a person's level of resilience. In this study, it was found that male students were more resilient than female students. In class X IPA SMA Negeri 1 Labuhan Deli, Academic Year 2021/2022.